The Effect of Garlic (Allium sativum) as Supplementary Feed on Growth Performance of Cherry Valley Ducks (Anas platyrhynchos domesticus) - Conniey, Fay Komilus; Maizatul Nazirah, Zainal-Abidin; Muslimatun, Arizal; Nur Syakirah Hanim, Mohd Khairi (2018)
The study was conducted to investigate the effect of garlic (Allium sativum) at the concentration of 0 %, 1% and 3% on growth performance of 27 Cherry Valley ducks (Anas platyrhynchos domesticus). The ducks were housed in battery cages with 3 ducks per partition of cages with access to water and diets for 2 weeks adjustment period and later, 4 weeks for feeding trial. Proximate analysis like moisture, crude protein, crude lipid, crude fibre, ash and nitrogen free extract were conducted on feed samples prior to feeding experiment while body weight gain, feed conversion ratio, feed intake and mortality rate were parameters used to measure growth performances. Data obtained were analysed by using one way ANOVA of IBM SPSS Statistic version 22. Moisture and crude lipid showed significant difference (p < 0.05) among treatments. There were no significant differences of protein, ash, fibre and nitrogen free extract for all treatments. Sampling of growth performance parameters were taken every 7 days for 4 weeks. Body weight gain showed significant difference (p < 0.05) among all treatments. There were no significant differences (p > 0.05) among all treatments in feed intake, mortality rate and feed conversion ratio. It can be concluded that feed supplemented with 1% garlic is suitable to improve growth performance of Cherry Valley ducks within 4 weeks of the feeding trial.